2015
DOI: 10.1093/rpd/ncv432
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Scatter Correction for Grid-Less Bedside Chest Radiography: Performance for a Chest Phantom

Abstract: The aim of this work was to experimentally compare the contrast improvement factors (CIFs) of a newly developed software-based scatter correction to the CIFs achieved by an antiscatter grid. To this end, three aluminium discs were placed in the lung, the retrocardial and the abdominal areas of a thorax phantom, and digital radiographs of the phantom were acquired both with and without a stationary grid. The contrast generated by the discs was measured in both images, and the CIFs achieved by grid usage were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 9 publications
2
43
0
9
Order By: Relevance
“…Eventual damage requires grid installation and replacement, and related costs. To overcome these limitations, researchers developed software that provides scatter correction without the physical use of a grid ( 4 5 6 7 ). The technology enables estimation of the scatter signal and calculation of the grid effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventual damage requires grid installation and replacement, and related costs. To overcome these limitations, researchers developed software that provides scatter correction without the physical use of a grid ( 4 5 6 7 ). The technology enables estimation of the scatter signal and calculation of the grid effect.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the de-scattered raw image is processed by the post-processing software of the digital radiography system. Although the value of scatter correction in terms of physical properties using a phantom has been reported ( 6 7 ), no test of observer preference has been performed to facilitate clinical application of this software.…”
Section: Introductionmentioning
confidence: 99%
“…Scattered radiation degrades the image quality of these areas of obscured lung and, therefore, contrast in these areas may be restored by using a grid. A phantom study revealed similar results with software-based scatter correction by demonstrating greater contrast improvement in the heart and abdominal areas than the lung area ( 9 ). In comparison, the areas of the thoracic spine and azygoesophageal recess, of which considerable scattered radiation occurs, received the highest preference for the algorithm-applied image.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, a virtual grid technique using scatter correction software has been developed to improve image quality by reducing the effect of scattered X-rays ( 9 10 ). In this approach, an iterative estimation of the scatter signal through Monte Carlo simulations of water phantoms is conducted, and scatter correction is conducted by compensating the contrast loss due to scattered signals.…”
Section: Discussionmentioning
confidence: 99%
“…46 Fast Monte-Carlo methods maybe used to expedite the algorithm, as is done for mammography or BCT. 45,46,48 We are in communication with Microworks GmbH, Germany, 49 to build preliminary MPG gratings suitable for breast imaging. In the future, we anticipate building a prototype by modifying existing TLXI systems in Pennington Biomedical Research Center, LSU, and at the synchrotron source at Louisiana State University Center for Advanced Microstructures and Devices.…”
Section: Discussion and Future Workmentioning
confidence: 99%